1984
DOI: 10.1007/bf02205590
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter and structural stability: mechanisms and implications for management

Abstract: Summary The stability of pores and particles is essential for optimum growth of plants. Two categories of aggregates macro-(> 250 }.Lm) and micro-« 250 }.Lm) depend on organic matter for stability against disruptive forces caused by rapid wetting. Dispersion of clay particles from microaggregates is promoted by adsorption of complexing organic acids which increase the negative charge on clays. The acids are produced by plants, bacteria and fungi. However, the dispersibility of clay in microaggregates is offset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
439
0
58

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,455 publications
(565 citation statements)
references
References 35 publications
28
439
0
58
Order By: Relevance
“…The difference in the degree of soil organic matter decomposition among different particle-size aggregates provides us an opportunity for understanding the formation mechanism of soil aggregates. Currently, various models have been employed to explain the formation of aggregates [61][62][63]. Our results seem to suggest that the formation of larger particle-size aggregates in soil is prior to that of smaller particle-size aggregates.…”
Section: Soc Turnover Times For Different Particle-size Aggregatesmentioning
confidence: 54%
“…The difference in the degree of soil organic matter decomposition among different particle-size aggregates provides us an opportunity for understanding the formation mechanism of soil aggregates. Currently, various models have been employed to explain the formation of aggregates [61][62][63]. Our results seem to suggest that the formation of larger particle-size aggregates in soil is prior to that of smaller particle-size aggregates.…”
Section: Soc Turnover Times For Different Particle-size Aggregatesmentioning
confidence: 54%
“…However, the use of 100 m 3 ha -1 in the 2010/11 growing season induced no differences in GMD and MWD compared to mineral fertilizer, which can be associated, partly, to the predominance of the dispersing effect of the chemical elements (Medeiros (Oades, 1984) on the aggregating effects observed in the second year. Thus, the continuous use of mineral fertilizers over time can reduce soil aggregate stability (Matos et al, 2008).…”
Section: Resultsmentioning
confidence: 92%
“…Although there are some trends with particle size, it is also evident that C pools The goal of aggregate-based soil fractionation is to isolate C pools according to their location in different soil physical structures, based on a conceptual model of stabilization of C inputs in microaggregates that cycle with macroaggregates (e.g., Oades 1984;Golchin et al 1994b;Jastrow et al 1998;Six et al 2000a;Six et al 2000b). Based in part on work by Golchin et al (1994b) and Cambardella and Elliot (1994), Six et al (2000a) developed a fractionation scheme designed to separately isolate SOM found inside and between aggregates of different sizes and stabilities.…”
Section: Fractionation Of Soil Organic Mattermentioning
confidence: 99%